Development of e-module based on local wisdom to improve science literacy and reading literacy - Legian Setyorini; Sri Haryani; Endang Susilaningsih (Pascasarjana Universitas Negeri Medan, 2022)
This research is motivated by (1) the results of reading literacy and science literacy in PISA, which is still low, and (2) technology and cultural-based learning media have not been developed by private high school chemistry teachers in Semarang. This research aims to develop a feasible E-module based on the local wisdom of spice drinks that can improve reading literacy and learners' science literacy. This research is a research and development with a 3-D model, which includes defining, designing, and developing. This study collects data through observation, questionnaires, and testing. The research instruments used are material expert validation sheets, multimedia expert validation, observation sheets, and instruments about reasoned multiple choice. The study subject was eight students of XI MIPA Kebon Dalem high school. Expert validation results of the material showed 92.85% (very valid). The validation results of media experts showed 85.71% (valid). E-modules are declared effective because there is an increase in the completion of learners' learning outcomes after using E-modules. E-Module based on local wisdom of spice drinks can visualize the factors that affect the rate of reaction material. So, it can be concluded that E-modules based on local wisdom spice drinks developed are worth using to improve learners' reading and science literacy.Keywords:E-module, Local wisdom, Reading literacy, Spice drinks, Science literacy